Enabling precision medicine with biomarkers of response to treatment in atopic dermatitis: where are we now? A narrative review - Chiricozzi, Andrea; Levi, Anna; Palladino, Chiara; Girolomoni, Giampiero (Frontiers in Medicine, 2025)
Atopic dermatitis (AD) is a complex systemic disease characterized by high heterogeneity both at clinical and pathophysiology levels. While advances in drug development toward a more targeted approach are made, treatment and management of AD patients are still happening according to the one-size-fits-all approach. To enhance precision medicine in AD and improve care, identifying predicting factors of response to therapy driving tailored treatments will be of utmost importance. Here, we discuss the available evidence regarding predictive biomarkers, as well as their possible and still debated impact in clinical practice.